Bioecological features of Nigella sativa L. in different conditions of Uzbekistan - Mahmudov, A V; Abduraimov, O S; Erdonov, Sh B; Gayibov, U G; Izotova , L Yu (Plant Science Today, 2022)
The article is devoted to the study of bio-ecological features of black caraway (kalonji) in different conditions of introduction. The analysis of the periods of ontogenesis, the biology of flowering, fruiting (seed productivity) in different conditions of Uzbekistan was carried out. By results of phenological researches the differences of terms of phases of the vegetative period and its turn, by morphometric parameters are revealed. Emergence of buds in Nigella sativa under conditions of introduction is observed in the first decade of May, sometimes in the middle of May, depending on weather conditions of the year. The earliest flowering was on 18.05, the latest on 29.05. Fruiting takes place in early June to late June. The end of the growing season is observed in late June-early July. The duration of vegetation in Malguzar is 130-35 days, while in Botanical Garden it is 135-145 days. The real seed production per plant averages 51.9±3.94 in Botanical Garden conditions and 42.5±2.10 in Malguzar.